Recent Advances of MXenes‐Based Optical Functional Materials - Zhang, Yali; Ruan, Kunpeng; Guo, Yongqiang; Gu, Junwei (Advanced photonics research, 2023)
Transition metal carbides/nitrides/carbonitrides (MXenes) exhibit tremendous potential for optical applications due to their diverse elemental composition and adaptable structural properties. Based on introducing the preparation methods and optical properties of MXenes, this review focuses on the latest advances in MXenes‐based optical functional materials, and analyzes the performance enhancement mechanisms of MXenes‐based optical functional materials for photothermal conversion and photocatalysis. The key scientific and technical bottlenecks in the field of MXenes‐based optical functional materials are pointed out, and the future development trends and research directions of MXenes‐based optical functional materials are prospected. This review focuses on the latest advances of MXenes‐based optical functional materials, and analyzes the performance enhancement mechanisms of MXenes‐based optical functional materials for photothermal conversion and photocatalysis. MXenes‐based photothermal conversion materials can be specifically applied to desalination, wearable devices, and photothermal therapy, and MXenes‐based photocatalysis materials can be specifically applied to water treatment, H2 production, and CO2 reduction.